Taking perspective between Indonesia and Germany: the establishment of quo vadis house of worship - Mohammad Hamidi Masykur; Tanto Lailam; Ferio Ivan Mulyono (Legality : Jurnal Ilmiah Hukum, 2025)
This paper discusses about licensing the establishment of houses of worship. In practice, the licensing arrangements for worship in both countries have significant differences. Indonesia has a bureaucratic approach that is formal, administrative, and social and community-based. Indonesia specifically regulates the requirements for the establishment of houses of worship in PBM 9 & 8/2006. Administrative, technical, and special requirements are required to obtain licenses. However, PBM 9&8/2006 has a loophole for the rejection of houses of worship, thus potentially inhibiting freedom of worship. On the other hand, Germany takes an ecological, spatial, and architectural approach to licensing houses of worship. Germany adheres to BauGB as a regulation related to building construction by paying attention to FNP and B-Plan as guidelines. This normative juridical research uses comparative, conceptual, and statutory approaches. The main finding of this research is that the two countries have different approaches in considering permits for the establishment of houses of worship. It is found that the difference between the two lies in the aspects of regulation, characteristics, and the approach to resolving disputes over the establishment of houses of worship.